Systematic review on dental caries preventive and managing strategies among type 2 diabetic patients - Chen, Haoran; Hill, Robert; Baysan, Aylin (Frontiers in Oral Health, 2022)
Purpose The purpose of this systematic review was to evaluate current evidence to prevent and manage dental caries in patients with type 2 diabetes mellitus (T2DM). Methods Following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, the Participants, Intervention, Comparison, Outcomes and Study Design (PICOS) strategy was used to formulate a structured search: systematic search of PubMed, Cochrane Library, MEDLINE via Ovid, EMBASE, Scopus, Web of Science, and Lilacs without any date limit and/or language restrictions. Two independent reviewers performed data extraction and risk of bias assessments in the included studies. Data homogeneity was assessed according to interventions for treating dental caries in T2DM. Statistical analyses were performed with JMP®. Results Two studies out of 909 were included in the systematic review. Only quantitative studies involving topical applications for management of dental caries in patients with T2DM were included. One study assessed the effect of intensive oral hygiene care program including toothbrushing and interdental cleaning using interproximal brushes and/or dental floss and supragingival debridement by dental hygienist with educational brochures in T2DM, while another investigated the immunologically active salivary substitutes with using Oral Hygiene Instructions (OHI), mouthwash, and moisturizing gel for 6 months. Intensive oral hygiene care program or immunologically active salivary substitutes with using OHI, mouthwash, and moisturizing gel for 6 months were reported to reverse/arrest dental caries in patients with T2DM. Conclusion The current randomized controlled clinical trials demonstrated that regular extensive oral health education using interdental cleaning aids, mouthwash, moistening gel, and saliva substitutes including lactoperoxidase, lysozyme, glucose oxidase, and lactoferrin could control oral inflammation and contribute to the management of dental caries in patients with T2DM. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42020197507, identifier: CRD42020197507.